Structural challenges to adopt digital transformation in industrial organizations: A multiple case study - Imran Faisal; Shahzad Khurram; Butt Aurangzeab Fareed; Kantola Jussi (United States, 2025)
Digital Transformation requires significant changes in industrial organization’s setting to remain relevant in this fast-paced environment. This calls for modifications in their organizational structures. The existing organizational structures of industrial organizations are mechanistic, while, digital transformation needs organic and flexible organizational structure. Therefore, the main aim of this study is to identify the main challenges that industrial organizations face in the process of modifying their mechanistic structures into organic structures. To explore these challenges, we conducted multiple case study from three global industrial organizations. We interviewed 41 middle to high-level management personnel. The results of this study highlight six main challenges that industrial organizations need to cope for structural modifications. These challenges are structural rigidity, traditional hierarchy, silos, problems with resource allocations, organizational size and old-fashioned-leadership.
Keywords: Digital transformation, Organizational structures, Change management
Human Factors in Management and Leadership